A feasibility method of constructing bilayer device for enhanced regulation in the mid-to-far IR region. (March 2022) - Tan, Peiyu; Lu, Feifei; Han, Yuge
Abstract: A dual-layer structure combining the properties of two polymers is demonstrated to be efficient in strengthening the mid-to-far infrared modulation. Prior to the assembly of bilayer devices, the infrared adjustment capability of single-layer devices poly(3, 4-ethylenedioxythiophene) ( PEDOT )、poly(pyrrole) ( PPY ) and poly(aniline) ( PANI ) with different polymerization charges is scrutinized. The results exhibit that the optimal polymerization charge affording the highest reflectance variation is inconsistent between the mid-wavelength and long-wavelength bands in PEDOT and PPY devices. However, through the arrangement of deposition sequence and relative thickness of PEDOT and PPY coatings, a device with the reflectance contrast of 0.662 in the mid-wavelength and 0.281 in the long-wavelength bands was obtained utilizing a bilayer film PEDOT-0.2C/PPY-0.3C . Further FTIR and UV–Vis spectra show that the bilayer films are successfully formed and both polymers play a role in the electrochemical process. Different morphologies of bilayer films with reverse positions observed by SEM images account for the correlation between the infrared regulation performance and deposition sequence. Highlights: The infrared regulation ability of PEDOT、PPY、and PANI devices in the mid-wavelength and long-wavelength bands was analyzed. The reason why single layer devices cannot perform well in the dual bands simultaneously was dissected. The construction criteria of efficient bilayers for stronger infrared regulation was proposed. A device affording 0.662 and 0.281 in the mid-wavelength and long-wavelength bands was achieved by PEDOT/PPY bilayer film.